Near Me at Home: codesigning the use of video consultations for outpatient appointments in patients' homes. Issue 3 (27th August 2020) - Beattie, Michelle; Morrison, Clare; MacGilleEathain, Rebecah; Gray, Nicola; Anderson, Julie
Abstract : Reforming the delivery of outpatient appointments (OPA) was high on the healthcare policy agenda prior to COVID-19. The current pandemic exacerbates the financial and associated resource limitations of OPA. Videoconsulting provides a safe method of real-time contact for some remotely residing patients with hospital-based clinicians. One factor in failing to move from introduction of service change to its general adoption may be lack of patient and public involvement. This project, based in the largest Island in the Inner Hebrides of Scotland, aimed to codesign the use of the NHS Near Me video consulting platform for OPA to take place in the patient's home. A codesign model was used as a framework. This included: step 1—presenting a process flow map of the current system of using Near Me to public participants and establishing their ideas on various steps in the process, step 2—conducting numerous Plan, Do, Study, Act (PDSA) tests and creating a current process flow diagram based on learning and step 3—conducting telephone interviews and thematic analysis of transcripts (n=7) to explore participants' perceptions of being involved in the codesign process. Twenty-five adaptations were made to the Near Me at Home video appointment process from participants' PDSA testing. Four themes were identified from thematic analysis of participants' feedback of the codesign process, namely: altruistic motivation, valuing community voices, the usefulness of the PDSA cycles and the power of 'word of mouth'. By codesigning the use of Near Me with people living in a remote area of Scotland, multiple adaptations were made to the processes to suit the context in which Near Me at Home will be used. Learning from testing and adapting with the public will likely be useful for others embarking on codesign approaches to improve spread and sustainability of quality improvement projects.